Establishment of an efficient Agrobacterium tumefaciens-mediated transformation system for an Armillaria species, a host of the fully mycoheterotrophic plant Gastrodia elata - Su, Zhongxiang; Li, Hongjing; Xu, Yuxing; Zhang, Cuiping; Wu, Jianqiang; Lei, Yunting (Folia microbiologica, 2024)
The genus Armillaria (Basidiomycota, Agaricales, Physalacriaceae) comprises pathogenic fungi that cause root-rot disease in plants, as well as species with low pathogenicity, some of which are hosts of the fully mycoheterotrophic orchid plant Gastrodia elata (Orchidaceae). To investigate the mechanisms underlying such special interactions between Armillaria fungi and G. elata, it is crucial to establish genetic transformation platforms for the Armillaria fungi and G. elata. In this study, an Armillaria strain Arm37 was isolated from G. elata, which can form symbiosis with G. elata in axenic culture under laboratory conditions. A vector pYT-EV containing a cassette for hygromycin-resistance selection and a cassette for expressing or silencing target genes was constructed. An Agrobacterium tumefaciens-mediated transformation (ATMT) system for Arm37 was successfully developed and optimized to achieve a transformation efficiency of 32%. The ATMT system was successfully used to express the reporter genes eGFP encoding enhanced green fluorescent protein and GUS encoding β-glucuronidase and to effectively silence the endogenous gene URA3 encoding orotidine-5'-phosphate decarboxylase in Arm37. This ATMT system established for Arm37 provides an efficient genetic tool for exploring the Arm37 genes that are involved in the unique interaction between the Armillaria fungi and fully mycoheterotrophic plant G. elata.
Keywords: Gastrodia elata; Gene overexpression; RNA interference; Armillaria; Agrobacterium tumefaciens-mediated transformation